Utilization of Ageratum conyzoides Leaf Extract as a Natural Anesthetic for Sustainable Closed-System Transportation of Tinfoil Barb (Barbonymus schwanenfeldii) Fingerlings - Nursetia Aisyah; Eko Dewantoro; Rudi Alvian (Jurnal Penelitian Pendidikan IPA, 2026)
The transportation of tinfoil barb (Barbonymus schwanenfeldii) fingerlings is a critical stage in aquaculture production because transportation stress can increase metabolic activity, deteriorate water quality, and reduce fish survival. This study evaluated the effectiveness of billygoat-weed (Ageratum conyzoides) leaf extract as a natural anesthetic agent and determined its optimal concentration for closed-system transportation of tinfoil barb fingerlings. A Completely Randomized Design (CRD) consisting of five treatments, namely 0, 2, 3, 4, and 5 mg L⁻¹ extract concentrations with three replications, was applied. Transportation was conducted for 12 h under closed-system conditions. The observed parameters included behavioral responses, induction time, recovery time, hematocrit, blood glucose, survival rate, and water quality. The results showed that increasing extract concentrations accelerated induction time but prolonged recovery time among anesthetized treatments. The 5 mg L⁻¹ treatment produced the fastest induction time (19.25 ± 1.87 min), whereas the 2 mg L⁻¹ treatment resulted in the shortest recovery time (9.06 ± 0.45 min). Fish treated with 4 mg L⁻¹ extract exhibited the lowest post-transport blood glucose concentration (136.0 ± 16.3 mg dL⁻¹), the highest post-transport survival rate (93.3%), and retained 90.0% survival after a seven-day recovery period. Therefore, 4 mg L⁻¹ was identified as the optimal concentration for maintaining physiological stability and improving the survival of tinfoil barb fingerlings during closed-system transportation.